The Transformative Power of Forgiveness in Wendell Berry’s Port William Fiction: Moral Growth and Community Healing - Chaimae Habboub; Jianqing SONG (International Journal of Scientific Research and Innovative Studies, 2025)
This study examines the multifaceted nature of forgiveness in Wendell Berry's Port William fiction, focusing on three key works: Jayber Crow, "Praying Without Ceasing," and "Thicker than Liquor." Through close textual analysis and engagement with contemporary scholarship, this research demonstrates that Berry portrays forgiveness as a transformative force operating simultaneously on personal, familial, and societal levels. The study employs a methodological framework combining narrative analysis with virtue ethics to examine how Berry's interconnected narratives present forgiveness not as a singular act but as a complex moral achievement that profoundly influences both individual character and community relationships. Analysis of character development, narrative structure, and thematic patterns reveals Berry's broader vision of moral growth and social healing within the Port William community. This research contributes to ongoing discussions about the role of forgiveness in contemporary American literature while highlighting its significance in moral ecology and communal resilience. Keywords: Wendell Berry, forgiveness, moral transformation. Received Date: December 18, 2024 Accepted Date: January 09, 2025 Published Date: February 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/327 https://doi.org/10.5281/zenodo.14944143